Attitudes towards Mental illness among Pregnant Women AttendinGovernment on Women's Clinics in the Province of Ramallah and Al-Bireh (Journal Of Educational and Psychological Researches, 2015)
This study aimed to identify attitudes towards mental illness in pregnant female clients to clinics women in the province of Ramallah and Al Bireh, for this purpose applied to study procedures on a sample of (200) of pregnant mothers were selected a sample available, have reached results no statistically significant differences in the level of attitudes towards mental illness due to the variable age in mothers pregnant female clients to clinics for women. Ther were astatistically significant differences in the level of these trends depending on the variable-level scientific research for the benefit of pregnant class university students and older and then high school and so on all areas except the area of social interaction, The results also showed a statistically significant differences in the level of these attitudes towards mental illness due to a variable number of times the load on the field of treatment for the first time to download, and no statistically significant differences on the rest of the fields, and reached results are also statistically significant differences in the level of attitudes towards mental illness in Pregnant variable depending on the number of abortions and that the areas of social compliance and the total score for the lack of abortion, and there is no statistically significant differences depending on this variable on the rest of the fields.